Recurrent Cubital Tunnel Syndrome: A Critical Analysis Review. Issue 3 (8th March 2016) - Tang, Peter; Hoellwarth, Jason S.; Chauhan, Aakash
Abstract : Most patients (>90%) will have continued or recurrent symptoms after primary cubital tunnel release. Those patients with severe preoperative findings are at a higher risk of failure. Failed primary surgery may be due to diagnostic, technical, or biologic factors. Revision surgical interventions can provide relief, but there is no consensus on what is the optimal technique. The options for revision surgery include simple neurolysis, neurolysis with subcutaneous transposition, and neurolysis with submuscular transposition. Autogenous (vein) and non-autogenous nerve wraps may be placed around the nerve to prevent cicatrix reformation.